Rare Adult Case of Plastic Bronchitis in an Otherwise Healthy Adult - Elen Gravell; Emma Parkes; Shehnoor Tarique (Respirology Case Reports, 2025)
ABSTRACT Plastic bronchitis (PB) is characterised by the formation of airway plugs at any level of the respiratory tract. Severe forms of PB can result in airway obstruction. It is more commonly seen in children. PB is usually associated with an underlying lung disease, and the underlying pathophysiology of PB is poorly understood.